Seasonal incidence of aphid, Amphorophora ampullata Bukton (Homoptera: Aphididae) on fern, Hypolepis polypodioides (Blume) Hook (Hypolepidaceae) from Western Himalaya. (26th August 2016) - Reddy, S. G. Eswara; Kumari, Alka
Abstract: Seasonal incidence of aphid, Amphorophora ampullata on Hypolepis polypodioides was recorded throughout the year from November 2012 to November 2013 at weekly interval. Peak incidence of aphid was recorded during third week of November 2012 (25.94 ± 2.39 aphids/pinna), later the aphid population gradually decreased from December 2012 onwards and reached below threshold level during the last week of January (0.1 ± 0 aphids/pinna). The aphid population starts building up again from first week of February 2013 (1.6 ± 0.13 aphids/pinna) and attained its peak in the last week of August (32.17 ± 1.22 aphids/pinna) then decreased gradually in the first week of September (20.82 ± 4.70 aphids/pinna). Aphid densities again increased gradually from second week of September (21.62 ± 3.02 aphids/pinna) to November 2013 and reached maximum aphid densities during November (56.55 ± 4.34 aphids/pinna). Among weather parameters, aphid population showed significant positive correlation with relative humidity during morning hours.